Вікіпедія, як спосіб отримання інформації - Нечиталюк, Влада; Мина, Жанна (Видавництво Львівської політехніки, 2020)
This article describes the place of eencyclopedia in society, how people use Wikipedia to find the data they need. The main positive and negative aspects of using this publicly available resource are also given.
Keywords: вікіпедія; знання; інформація; пошук; отримання; дані; стаття; порівняння; недоліки; позитивні аспекти